A potential integral equations method for electromagnetic scattering by penetrable bodies. - De Doncker, P.
A method for computing the electromagnetic scattering by general inhomogeneous penetrable bodies is presented. The method is based on the volume equivalence principle and it uses the electromagnetic potentials as unknowns. The resulting coupled integral equations system is solved by the method of moments in combination with cubical and curvilinear meshes in the special case of purely dielectric scatterers. To show the accuracy of the method, numerical results of the transmitted and of the scattered fields are compared with existing analytical and experimental results
Keywords: MoM; Backscatter RCS; Coupled integral equations; Cubical meshes; Curvilinear meshes; Dielectric scatterers; Electromagnetic potentials; Electromagnetic scattering; Inhomogeneous penetrable bodies; Method accuracy; Method of moments; Potential integral equations method; Scattered fields; Transmitted fields; Volume equivalence principle